Acute doxorubicin (adriamycin) dosage does not reduce cardiac protein synthesis in vivo, but decreases diaminopeptidase I and proline endopeptidase activities - Zima, T; Tesar, V; Mantle, D; Koll, M; Patel, V; Richardson, P J; Preedy, V R (Experimental and molecular pathology, 2001)
Anthracycline antibiotics are effective anticancer agents but their use is limited due to unwanted adverse side effects. The toxic effects of doxorubicin (adriamycin) include the development of defined cardiac lesions leading to cardiomyopathy in some patients. This has been reported to be due to reductions in cardiac protein synthesis. However, virtually all of these previous studies have failed to consider the specific radioactivity of the precursor pool in their measurements or have carried out their studies in vitro. To further resolve the above we measured fractional rates of cardiac protein synthesis using the "flooding dose" method in rats treated with adriamycin (5 mg/kg body wt). Controls were identically treated and injected with saline. At 2.5 or 24 h after adriamycin injection, rates of protein synthesis were measured with a flooding dose of l-[4-(3)H]phenylalanine. Measurements included free (S(i)) and protein-bound (S(b)) phenylalanine-specific radioactivities, the protein synthetic capacity (RNA/protein ratio; C(s)), the fractional rates of protein synthesis calculated from the ratio S(b)/S(i), and the protein synthetic efficiency calculated from the ratio k(s)/C(s). Complementary analyses included assays of lysosomal (cathepsins B, D, H, and L and diaminopeptidases I and II) and cytoplasmic proteases (alanyl aminopeptidase, arginyl aminopeptidase, leucyl aminopeptidase, diaminopeptidase IV, tripeptidyl aminopeptidase, and proline endopeptidase). These enzymes constitute the most active proteases in this tissue and represent an index of protein degradation capacity in cardiac muscle. The results showed that in 2.5-h dosed rats, adriamycin had no effect on S(i), S(b), C(s), k(s), or k(RNA) (P > 0.05, not significant (NS) in all instances). In 2.5-h dosed rats, levels of diaminopeptidase I activity were reduced (P < 0.05), whereas the activities of other proteases were not significantly altered (NS in all instances). In 24-h dosed rats, adriamycin reduced cardiac S(b) (P < 0.001), which would normally be interpreted as a reduction in protein synthesis. However, S(i) was also decreased in 24-h adriamycin-injected rats (P < 0.025%). C(s) was not changed (NS). Consequently, the calculated k(s) and k(RNA) values were not significantly affected in 24-h adriamycin-dosed rats (NS). There were also significant reductions in proline endopeptidase activities in rats exposed for 24 h to adriamycin. The activities of other proteases were not significantly affected at this time point (NS in all instances). In conclusion, adriamycin reduces amino acid labeling of cardiac proteins, an effect that is a consequence of altered free phenylalanine-specific radioactivities. There was some evidence of limited altered intracellular proteolysis.
Keywords: Animals; Doxorubicin; Heart; serinové endopeptidasy; kathepsin C; proteosyntéza; Rats, Wistar; Serine Endopeptidases; protinádorová antibiotika; Phenylalanine; prolyloligopeptidasy; srdce; Prolyl Oligopeptidases; Antibiotics, Antineoplastic; fenylalanin; Male; doxorubicin; Protein Biosynthesis; krysa rodu Rattus; Enzyme Induction; enzymová indukce; zvířata; mužské pohlaví; Myocardium; myokard; Rats; potkani Wistar; Cathepsin C